Pendidikan Karakter Dalam Bab Menjauhi Maksiat Kitab Bidayatul Hidayah Karya Imam Al Ghozali - Roziqi, Ahmad Masrur (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
This study examines the concept of character education in the view of Imam Al-Ghazali as stated in the book of Bidayatul Hidayah, this study specializes in examining the chapter of Avoiding Maksiat. This study is motivated by the assumption of the urgency of building a superior and noble generation through the internalization of good values. Imam Al-Ghazali explicitly emphasizes the importance of attention to students as a strategic step in creating a generation of intellectuals with character. In order to dig deeper into these thoughts, this research uses a qualitative method with a literature review approach. Primary data is obtained from the book Bidayatul Hidayah by Imam Al-Ghazali, while secondary data comes from relevant supporting literature. The data analysis technique was conducted through content analysis, focusing on the identification of character education values listed in the chapter of Abstaining from Maksiat. The results show that character education, according to Imam Al-Ghazali, aims to instill good values that are realized through guarding the seven limbs such as the eyes, ears, tongue, stomach, genitals, hands, and feet from sinful acts. This approach emphasizes the importance of self-control as the main foundation in the formation of noble morals. This study also found that the concept of character education in Imam Al-Ghazali's perspective remains relevant to the needs of modern education, especially in forming individuals who have moral integrity and intellectual abilities. This study provides an important contribution in broadening insights into the application of character education based on classical Islamic values, as well as integrating these principles into contemporary educational paradigms